FACTORS AFFECTING HUMAN RESOURCE MANAGEMENT ACTIVITIES IN ENTERPRISES IN HUNG YEN PROVINCE - Nguyen Thi Mo; Hoang Thị Hue; Bui Thị Thu Thuy (Journal of Applied Science and Technology, 2019)
This study focuses on analyzing the factors affecting human resource management in enterprises in Hung Yen province. The data of the study was collected through a survey of 270 directors, managers and employees. The study used a reliability testing method with Cronbach’s alpha coefficient, exploratory factor analysis and linear regression. The results show that internal environmental factors and external environment have a positive impact on human resource management and there is no difference according to age, gender, professional level and position in the management. human resources at businesses.